Encyclopedia of white-collar and corporate crime - Salinger, Lawrence M. (Sage Publications, 2013)
This work incorporates information about a variety of white-collar crimes, and provides examples of persons, statutes, companies, and convictions. Each entry offers a thorough and thoughtful summary of the topic. Describes specific elements of corporate law and the various illegal acts to which they apply and brief biographical sketches, primarily focused on how they relate to the study of white-collar crime.